Age-specific familial risks in cancer as clues to germline genetic and environmental causes: focus on colorectal, endometrial, prostate, kidney, breast and lung cancers - Kari Hemminki; Asta Försti; Otto Hemminki; Rodney J. Scott; Akseli Hemminki (Hereditary Cancer in Clinical Practice)
Abstract Background The Swedish Family-Cancer Database (FCD) is the largest source of data on familial cancer in the world, including practically complete family structures and individual cancer diagnoses from the high-quality cancer registry. We present a novel application of FCD by analyzing age-specific familial risks and interpreting them through likely causes, such as germline pathogenic variants and/or environmental exposures. Main body The basic assumption for this approach is that a discrete familial clustering in a narrow age-interval is not random but may provide causal clues. For this analysis we selected reasonably common cancers to meaningfully scrutinize familial risk through adulthood in which cancers are diagnosed, that included colorectal (CRC) and endometrial cancers, prostate and kidney cancers and breast and lung cancers. The interpretation is based on the literature. The highest familial relative risks for CRC and endometrial cancers were found at ages 40–44 years, matching the peak impact of mismatch repair gene mutations. However endometrial cancer showed also a small early onset component which could not be explained. Age-related familial risks for breast, prostate and kidney cancers also matched data from large-scale sequencing; these included the early onset component in kidney cancer which was likely due to VHL mutations. Age distribution of familial lung cancer was unique in showing a wide peak extending from middle to old ages, which would be consistent with a combination of direct genetic effects and indirect influence on inheritance of smoking dependence. Conclusions The present review of age-specific familial risks and age-of-onset data from the literature may allow an interpretation that the familial and germline landscapes are reasonably harmonious for relatively early onset cancers but at higher ages no discrete peaks can be found which may implicate attenuated impact of high-risk genes and polygenic influence.